2017
DOI: 10.1093/gerona/glx069
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate, But Not Extended, Afternoon Naps May Preserve Cognition in Chinese Older Adults

Abstract: Results suggest that afternoon naps less than 90 minutes may be beneficial for cognition in older adults, while long afternoon naps may be detrimental.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 30 publications
(51 reference statements)
4
36
0
Order By: Relevance
“…Importantly, in laboratory settings, nap duration can be controlled, and lab‐based studies had small samples of healthy older adults, rather than community‐based samples with greater medical morbidity. To a degree, our results are also in line with studies linking moderate‐duration naps (30‐90 minutes) with better cognition 13 and improvements in cognition . However, those studies tied moderate‐duration naps to better performance on a combined score from three cognitive assessments.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Importantly, in laboratory settings, nap duration can be controlled, and lab‐based studies had small samples of healthy older adults, rather than community‐based samples with greater medical morbidity. To a degree, our results are also in line with studies linking moderate‐duration naps (30‐90 minutes) with better cognition 13 and improvements in cognition . However, those studies tied moderate‐duration naps to better performance on a combined score from three cognitive assessments.…”
Section: Discussionsupporting
confidence: 90%
“…However, conflicting findings may be due to measurement differences. For instance, a UK‐based study found napping to be protective with respect to cognitive decline, but only included older adults who were cognitively unimpaired at baseline and did not examine napping intention or frequency; other studies in China only assessed afternoon (ie, post‐lunch) nap duration …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that a more detailed assessment of napping is important, including the analysis of the frequency and duration of the naps. Short‐term naps (<90 min) are beneficial to health (Li et al, ), whereas long‐term and a higher frequency of naps may be detrimental (Cross et al, ; Li et al, ; Wang, Hao, Bo, & Li, ).…”
Section: Discussionmentioning
confidence: 99%